Rohingya infulex: A multidimensional experience of the local host community - Partha, Ranjan and Ghosh, Dipanwita (Man in India)
The inter relationship between refugees and local host community is given paramount importance in the academic discussing of refugees. While many researches have been conducted in development and academic arena, little work has been done on the perspectives of local people living in the surrounding area so of the Rohingya camps and how they re adapting to the Rohingya influx. This article discusses low the local lost community of Bangladesh differing by class and gender are adapting to the Rohingya influx, or the kinds of everyday experiences they are encountering without limiting their expiries to they binary division of advantage and dish antae of Rohingya influx.- Reproduced
Keywords: Pano, Kondh, Identity, Tribe caste, community, Custom